Rituals and Traditional Events in the Modern World - Frost, Jennifer (Routledge Advances in Event Research Series, 2014)
Many events have evolved over centuries, drawing on local customs and conditions. However, as the world becomes increasingly globalised, traditional events and the identities they support are increasingly being challenged and rituals may be lost. Reacting against this trend towards homogeneity, communities strive to preserve and even recreate their traditional events, which may require rituals to be resurrected or reinvented for a new audience.The aim of this book is to explore the role of traditional events and rituals in the modern world. The 16 chapters cover a range of case studies of the